Gadolinium tissue deposition in the periodontal ligament of mice with reduced renal function exposed to Gd-based contrast agents. - Delfino, Riccarda; Biasotto, Matteo; Candido, Riccardo; Altissimo, Matteo; Stebel, Marco; Salomè, Murielle; van Elteren, Johannes T; Vogel Mikuš, Katarina; Zennaro, Cristina; Šala, Martin; Addobbati, Riccardo; Tromba, Giuliana; et al. (Toxicol Lett, 2019)
Gadolinium deposition in tissue is linked to nephrogenic systemic fibrosis (NSF): a rare disorder occurring in patients with severe chronic kidney disease and associated with administration of Gd-based contrast agents (GBCAs) for Magnetic Resonance Imaging (MRI). It is suggested that the GBCAs prolonged permanence in blood in these patients may result in a Gd precipitation in peripheral or central organs, where it initiates a fibrotic process. In this study we investigated new sites of retention/precipitation of Gd in a mouse model of renal disease (5/6 nephrectomy) receiving two doses (closely after each other) of a linear GBCA. Two commercial GBCAs (Omniscan® and Magnevist®) were administered at doses slightly higher than those used in clinical practice (0.7 mmol/kg body weight, each). The animals were sacrificed one month after the last administration and the explanted organs (kidney, liver, femur, dorsal skin, teeth) were analysed by X-ray fluorescence (XRF) at two synchrotron facilities. The XRF analysis with a millimetre-sized beam at the SYRMEP beamline (Elettra, Italy) produced no detectable levels of Gd in the examined tissues, with the notable exception of the incisors of the nephrectomised mice. The XRF analyses at sub-micron resolution performed at ID21 (ESRF, France) allowed to clearly localize Gd in the periodontal ligaments of teeth both from Omniscan® and Magnevist® treated nephrectomised mice. The latter results were further confirmed by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). The study prompts that prolonged permanence of GBCAs in blood may result in Gd retention in this particular muscular tissue, opening possibilities for diagnostic applications at this level when investigating Gd-related toxicities.
Keywords: Animals; Contrast Media; Disease Models, Animal; Dose-Response Relationship, Drug; Female; Gadolinium; Gadolinium DTPA; Magnetic Resonance Imaging; Mice; Nephrogenic Fibrosing Dermopathy; Periodontal Ligament; Renal Insufficiency; Tissue Distribution

Light element distribution in fresh and frozen-thawed human ovarian tissues: a preliminary study. - Pascolo, Lorella; Venturin, Irene; Gianoncelli, Alessandra; Bortul, Roberta; Zito, Gabriella; Giolo, Elena; Salomè, Murielle; Bedolla, Diana E; Altissimo, Matteo; Zweyer, Marina; Ricci, Giuseppe (Reprod Biomed Online, 2018)
RESEARCH QUESTION: Does synchrotron X-ray fluorescence (XRF) provide novel chemical information for the evaluation of human ovarian tissue cryopreservation protocols? DESIGN: Tissues from five patients undergoing laparoscopic surgery for benign gynaecological conditions were fixed for microscopic analysis either immediately or after cryopreservation. After fixation, fresh and slowly frozen samples were selected by light microscopy and transmission electron microscopy, and subsequently analysed with synchrotron XRF microscopy at different incident energies. RESULTS: The distributions of elements detected at 7.3 keV (S, P, K, Cl, Fe, and Os) and 1.5 keV (Na and Mg) were related to the changes revealed by light microscopy and transmission electron microscopy analyses. The light elements showed highly informative findings. The S distribution was found to be an indicator of extracellular component changes in the stromal tissues of the freeze-stored samples, further revealed by the transmission electron microscopy analyses. Low-quality follicles, frequent in the freeze-thawed tissues, showed a high Na level in the ooplasm. On the contrary, good-quality follicles were detected by a homogeneous Cl distribution. The occurrence of vacuolated follicles increased after cryopreservation, and the XRF analyses showed that the vacuolar structures contained mainly Cl and Na. CONCLUSIONS: The study demonstrates that elemental imaging techniques, particularly revealing the distribution of light elements, could be useful in establishing new cryopreservation protocols.
Keywords: Cryopreservation; Female; Humans; Microscopy, Electron, Transmission; Organ Preservation; Ovarian Follicle; Ovary

X-ray fluorescence elemental mapping and microscopy to follow hepatic disposition of a Gd-based magnetic resonance imaging contrast agent. - Delfino, Riccarda; Altissimo, Matteo; Menk, Ralf Hendrik; Alberti, Roberto; Klatka, Tomasz; Frizzi, Tommaso; Longoni, Antonio; Salomè, Murielle; Tromba, Giuliana; Arfelli, Fulvia; Clai, Milan; Vaccari, Lisa; et al. (Clin Exp Pharmacol Physiol, 2011)
1. Spatially resolved X-ray fluorescence (XRF) spectroscopy with synchrotron radiation is a technique that allows imaging and quantification of chemical elements in biological specimens with high sensitivity. In the present study, we applied XRF techniques at a macro and micro level to carry out drug distribution studies on ex vivo models to confirm the hepatobiliary disposition of the Gd-based magnetic resonance imaging contrast agent B22956/1. 2. Gd presence was selectively quantified allowing the determination of the time dependent disappearance of the drug from blood and its hepatic accumulation in mice after administration. Elemental mapping highlighted the drug distribution differences between healthy and diseased livers. XRF microanalyses showed that in CCl(4) -induced hepatitis, B22956/1 has greatly reduced hepatic accumulation, shown as a 20-fold reduction of Gd presence. Furthermore, a significant increase of Fe presence was found in steatotic compared with healthy livers, in line with the disease features. 3. The present results show that XRF might be useful in preclinical pharmacological studies with drugs containing exogenous elements. Furthermore, quantitative and high-sensitivity elemental mapping allows simultaneous detection of chemical variation, showing pathological conditions. This approach was useful in suggesting reduced B22956/1 accumulation in steatotic livers, thus opening possible new diagnostic perspectives for this drug.
Keywords: Animals; Contrast Media; Fatty Liver; Female; Gadolinium; Hepatitis; Iron; Liver; Magnetic Resonance Imaging; Mice; Mice, Inbred CBA; Organometallic Compounds; Spectrometry, X-Ray Emission